Accuracy of clinical diagnosis in meniscal tears - Thakur, Abhishek Kumar (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Meniscal injuries of the knee are common indications for arthroscopic knee surgery. Most of the meniscal tears can be diagnosed by clinical evaluation alone. This study aims to test the accuracy of the commonly performed tests for meniscal tears in our set up.Method: This was a prospective observational study of 32 symptomatic knees that underwent clinical evaluation followed by arthroscopy. The sensitivity, specificity and diagnostic accuracy of three clinical tests (McMurray’s test, Apley’s compression test and Joint line tenderness) were calculated against arthroscopic findings.Result: Among clinical tests, maximum sensitivity (94.44%) was with Joint Line Tenderness for Medial Meniscus Tear (MMT) and minimum (54.54%) with Apley’s Compression Test for Lateral meniscus Tear (LMT). Specificity was maximum (90.48%) with Joint Line Tenderness for LMT and minimum (64.28%) with Apley’s Compression Test for MMT. Diagnostic accuracy was maximum (90.6%) with McMurray’s test for LMT and minimum (75%) with Apley’s Compression Test for MMT and LMT.Conclusion: All three clinical tests (McMurray’s, Apley’s compression and Joint line tenderness) were found reliable for diagnosing meniscus tears. Joint Line Tenderness had the best diagnostic accuracy followed by McMurray’s test.